Determination of Helicobacter pylori by ELISA: single-center experience - Bakyt, L.G.; Zhumina, A.G. (KSU Publ., 2020)
Identifying the causes of helicobacteriosis, their timely diagnosis, and the choice of the correct treatment tactic will help improve the population health and increase life expectancy. This article is devoted to studying the presence of Helicobacter pylori antigens in the blood plasma of patients living in the Zhezkazgan city. The aim of the project is to determine the distribution of Helicobacter pylori by ELISA method. The result of our research shows that the presence of antibodies to Helicobacter pylori was found in 20 blood plasma samples from 45 analyzed, which is 44.45 % from overall samples number. The majority of positive results among Zhezkazgan city residents were detected in female samples (54.5 %), then in male (34.7 %) while in two previous studies the prevalence of positive results was in men or identical percentages in men and women. The most of positive results were detected in the residents at the age from 0 to 18 (50 %) and at the age who over 60 (66.6 %). The results identified that in Zhezkazgan city the Helicobacter pylori infection prevailed in the category of preschoolers and scholars and also among the old people, while the working population has the lower positive results (39.2 %).
ИФА әдісімен Helicobacter pylori анықтау: бір орталықтың тәжірибесі
Определение Helicobacter pylori методом ИФА: опыт одного центра
Keywords: Helicobacter pylori; distribution; ELISA; antibody